Law Enforcement in The Eradication of Criminal Acts in Children and Youth Generations - Yuniar F Danil; Agung Faris Sintusa; Teguh Bayu Aji (Faculty of Law, Universitas Jenderal Soedirman, 2022)
Drug abuse is an extraordinary crime that destroys the order of family life,society and the school environment, even directly or indirectly threatening thecontinuity of development and the future of the nation and state. In Indonesia,narcotics have reached an alarming level and can threaten the security andsovereignty of the country. Many cases are caused by drug use cases. If viewedfrom the juridical aspect, the existence of narcotics is legal. Law Number 35 of2009 concerning Narcotics only prohibits the use of narcotics that are not inaccordance with the provisions of the law. The method used in this article uses library research with descriptive analysis specifications and uses a statutory approach and a case approach. While the materials used are primary legal materials, secondary legal materials and thesis legal materials with data collection techniques based on library research and technical data analysis using deductive methods.Keywords: Children, Youth Generations, Drug Abuse, Crime